EFISIENSI SEBAGAI BASIS KEBIJAKAN PENYELENGGARAAN PERUMAHAN RAKYAT - Erica Soeroto (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
Compared to other countries, housing financing in Indonesia is relatively left behind. In Indonesia, housing financing is dominantly by banking’s mortgage loan. Furthermore, the ratio of home loan to GDP of the country is still insignificant. If we compare to other countries’ banking sector, Indonesia’s banking sector is less efficient. This could be observed from the interest rate spread of the banking sector. This article argues that, housing policy in Indonesia should focus on improving housing financing efficiency through: efficient primary housing financing, liquid and stable bond market, and supporting regulation based on cost and benefit analysis; in order to provide affordable housing for low income people in Indonesia. Keywords: housing financing; housing policy; banking sector efficiency; Indonesia